INVESTIGATION ON THE IMMUNOLOGICAL EFFECTS OF REGULAR PHYSICAL ACTIVITY - Berki, Alexandra Réka; Arany, Attila Csaba; Jámbor, Ilona; Szabó, Krisztina; Mile, Marianna; Makra, Gabriella; Csiki, Zoltán; Balogh, László; Papp, Gábor (Stadium - Hungarian Journal of Sport Sciences, 2019)
Introduction: Effects of physical activity on immune functions may largely depend on the type of activity, its intensity and duration. However, little information is available regarding the immunological effects of sporting activities in older ages. The aim of our study was to examine the changes in a wide spectrum of lymphocyte subtypes after a period of regular workout among healthy women of different ages.Methods: In our study, we enrolled 16 elderly women (between ages of 60-75 years) formerly not engaged in regular physical activity, who took part in lightweight conditioning gymnastic exercise program. Eight young athletes and 26 young adults with sedentary lifestyle served as controls. The percentages of peripheral NK, NKT cells, T and B lymphocyte subtypes were determined by flow cytometry based on the staining of extracellular markers and intracellular cytokines.Results: Lymphocyte subgroups did not differ between the groups of young athletes and young adults with sedentary lifestyle. However, in elderly women, levels of NKT cells were lower, while ratios of T helper / T cytotoxic cells were higher compared to younger individuals. At the end of exercise program, in elderly women, percentages of naive B cells decreased, while levels of switched-memory B cells increased. Furthermore, proportions of Th2 cells increased, while levels of immunosuppressive CD4+CD127-CD25bright Treg cells decreased as the result of regular exercise.Conclusion: Differences observed after lightweight exercise programs reflect a presumably enhanced immunoreactivity and increased ability for immune responses in older ages.